Characterizing seasonal changes in the reproductive activity of Culex mosquitoes throughout the fall, winter, and spring in Ohio - Alden Siperstein; Laura W. Pomeroy; Sydney Robare; Lucas Sarko; Hannah Dehus; Taylor Lowmiller; Lydia Fyie; Megan E. Meuti (Parasites & Vectors, 2023)
Abstract Background Culex mosquitoes are the primary vectors of West Nile virus (WNV) across the USA. Understanding when these vectors are active indicates times when WNV transmission can occur. This study determined the proportion of female Culex mosquitoes that were in diapause during the fall and winter and when they terminated diapause and began blood feeding in the spring. Methods Mosquitoes were collected from parks using various traps and/or aspirated from culverts in Franklin County, Ohio, from October to mid-May from 2019 to 2022. Culex mosquitoes were morphologically identified to species, and the ovaries of females were dissected to determine their diapause and parity statuses. Results By early October 2021, roughly 95% of Culex pipiens collected in culverts were in diapause and 98% of Cx. erraticus were in diapause. Furthermore, gravid and blood-fed Culex salinarius, Cx. pipiens, and Cx. restuans were collected in late November in 2019 and 2021 in standard mosquito traps. In the winter of 2021, the proportions of non-diapausing Culex decreased within culverts. The last non-diapausing Cx. erraticus was collected in late December 2021 while the final non-diapausing Cx. pipiens was collected in mid-January 2022, both in culverts. Roughly 50% of Cx. pipiens terminated diapause by mid-March 2022, further supported by our collections of gravid females in late March in all 3 years of mosquito collection. In fact, male mosquitoes of Cx. pipiens, Cx. restuans, and Cx. territans were collected by the 1st week of May in 2022, indicating that multiple species of Culex produced a second generation that reached adulthood by this time. Conclusions We collected blood-fed and gravid Culex females into late November in 2 of the 3 years of our collections, indicating that it might be possible for WNV transmission to occur in late fall in temperate climates like Ohio. The persistence of non-diapausing Cx. pipiens and Cx. erraticus throughout December has important implications for the winter survival of WNV vectors and our overall understanding of diapause. Finally, determining when Culex terminate diapause in the spring may allow us to optimize mosquito management programs and reduce the spread of WNV before it is transmitted to humans. Graphical Abstract